PENDEKATAN SISTEM DINAMIS DALAM PENYUSUNAN STRATEGI OPTIMAL UNTUK PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN PETANI DESA TAMPINGMOJO - Reznandya Putri Septyawati; Hery Murnawan (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2025)
Agriculture is a crucial sector in Tampingmojo Village, where approximately 60.94% of the area comprises rice fields. However, declining crop productivity each year due to factors like fertilizer use, seed quality, and cultivation practices poses a threat to local food security. This research aims to formulate an optimal scenario model to enhance farmer productivity and profits using a dynamic systems approach. The model was developed through stages including CLD and SFD construction, validation, sensitivity analysis, scenario establishment, and selection of the best scenario. Fertilizer and seed variables were prioritized due to their significant impact on productivity and profit. Historical data from 2019–2023 served as the base model for validation and testing. Simulation using STELLA revealed that Scenario 3, applying optimal doses of urea and phonska combined with organic fertilizer substitution, is the most effective. This scenario increased productivity by 18.10% (Inpari, MT 1), 19.95% (Ciherang, MT 2), and 21.94% (Pioneer, MT 2 & 3), while raising profits by 78.72% (Inpari, MT 1 & 2) and 63.73% (Bisi, MT 2 & 3) compared to existing conditions. Thus, this scenario is recommended as a policy direction to support improved productivity, farmer income, and strengthen local food security.